The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/jp1116855
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Organic Asymmetric Donors D1–A–D2 Possessing Broad Absorption Regions and Suitable Frontier Molecular Orbitals to Match Typical Acceptors toward Solar Cells

Abstract: A series of donors have been designed based on three building blocks, i.e., triphenylamine (TPA), 4,7-di(thiophen-2-yl)benzo[c][1,2,5]thiadiazole (DBT), and oligothiophenes (5Th), to investigate suitable molecules toward solar cell materials. The donors are built by two donor fragments (TPA as D1 and 5Th as D2) and one acceptor fragment (DBT as A) in three topologies with or without linkages and electron-withdrawing groups. Their electronic and optical properties have been characterized by the PBE0/6-31G(d,p) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 89 publications
(56 reference statements)
2
30
0
Order By: Relevance
“…The BHJ-OSC was fabricated based on this OSM as the donor, PCBM as the acceptor. A higher PCE (2.56% vs. 1.70%, respectively) was achieved when used PC 70 BM as the acceptor. To enhance PV performance, Sharma and co-workers replaced tetrahydrofuran (THF) by THF-DIO (1,8-diiodooctane) as solvent and the device was also treated with thermal annealing.…”
Section: π-Linkage With Arene and Heterocyclementioning
confidence: 89%
See 1 more Smart Citation
“…The BHJ-OSC was fabricated based on this OSM as the donor, PCBM as the acceptor. A higher PCE (2.56% vs. 1.70%, respectively) was achieved when used PC 70 BM as the acceptor. To enhance PV performance, Sharma and co-workers replaced tetrahydrofuran (THF) by THF-DIO (1,8-diiodooctane) as solvent and the device was also treated with thermal annealing.…”
Section: π-Linkage With Arene and Heterocyclementioning
confidence: 89%
“…The adoption of D-π-A structure with a coplanar bridge not only facilitates the electronic coupling between the donor and acceptor blocks, but also extends the spectral response to the red region. BHJ device based on 43:C 70 showed a PCE of 3.82% with J SC of 9.53 mA cm −2 , V OC of 0.83 V, FF of 0.48.…”
Section: π-Linkage With Arene and Heterocyclementioning
confidence: 99%
“…E(D) and E(D) are the energies of the cationic electron donor at the neutral geometry and optimal cation geometry, respectively. The λ ext designates the variation in the surrounding medium due to the electronic and nuclear polarizations effects [71][72][73]. However, it is confirmed that it is not easy to estimate quantitatively the λ ext in solid state.…”
Section: Interfacial Electron Transfer: Marcus Theorymentioning
confidence: 99%
“…17 In this work, the spectral absorption of the designed polymers was therefore calculated using the O3LYP functionals and the 6-311G** basis set using ground-state geometries optimized by the B3LYP/6-311G** method. The reorganization energy [33][34][35] was obtained from the B3LYP/6-311G** functional and basis set. The transfer integral 36 used to obtain the charge transport by the polymers was calculated using the DFT-M062X/6-31G** method and basis set.…”
Section: Computational Detailsmentioning
confidence: 99%